Experiências de aprender a dar aulas de música antes do ingresso em curso de licenciatura - Oliveira, João Paulo de Rezende (2019)
The study discusses the musical-pedagogical preparation of four student music teachers from Federal University of Uberlândia before their entrance to the music teacher training course. The research aims to analyse how these pre-service student music teachers built their own ways of teaching before their undergraduate course. The research adopted a qualitative approach. The method employed was a single case study and the procedure for data collection was based on semi-structured interviews. To understand how these student music teachers learned how to become a non-qualified music teacher, we used the theory of experiencial learning as a theoretical framework. By supporting the existence of three musical-pedagogical formation stages (before, during, after undergraduate), we identified three stages across the first moment: (1) building a musical-pedagogical model for music lessons; (2) early experiences in classroom; (3) stabilizing the pedagogical work. Other studies are suggested as a way to expand the knowledge on the subject-matter which is seldom discussed in the area of music pedagogy.